Exploring the effect of remote substituents and solution structure on the luminescence of three lanthanide complexes - Tropiano, M; Blackburn, O; Tilney, J; Hill, L; Sørensen, T; Faulkner, S (Elsevier, 2015)
Sensitized luminescence from trivalent lanthanide ions relies on an appropriate energy match between the sensitizer’s excited state (triplet or singlet) and the lanthanide excited state manifold, and also an efficient mechanism of energy transfer between the two. Here, the effect of remote substituents on the luminescence properties of a series of related lanthanide complexes has been investigated. The sensitized lanthanide centered emission is not invariably found to occur following excitation of all chromophores in all systems, and it is shown that only the most structurally congested of the systems investigated exhibited pronounced solvatochromism.